2020
DOI: 10.7554/elife.54838
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Nrxn1α within excitatory forebrain circuits drives value-based dysfunction

Abstract: Goal-directed behaviors are essential for normal function and significantly impaired in neuropsychiatric disorders. Despite extensive associations between genetic mutations and these disorders, the molecular contributions to goal-directed dysfunction remain unclear. We examined mice with constitutive and brain region-specific mutations in Neurexin1α, a neuropsychiatric disease-associated synaptic molecule, in value-based choice paradigms. We found Neurexin1α knockouts exhibited reduced selection of beneficial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 97 publications
1
17
0
Order By: Relevance
“…Finally, we also noted that PL::A-DMS inhibition disrupted the natural slowing of trial initiations observed following negative outcomes (Fig. 7f,h) 24,27,28 . These results support divergent fronto-striatal control of outcome-related strategies, with PL::P-DMS activity mediating positive reinforcement and PL::A-DMS driving choice persistence in the face of negative outcomes.…”
Section: Pl::dms Pathways Divergently Control Response Strategies To Positive and Negative Outcomessupporting
confidence: 58%
See 2 more Smart Citations
“…Finally, we also noted that PL::A-DMS inhibition disrupted the natural slowing of trial initiations observed following negative outcomes (Fig. 7f,h) 24,27,28 . These results support divergent fronto-striatal control of outcome-related strategies, with PL::P-DMS activity mediating positive reinforcement and PL::A-DMS driving choice persistence in the face of negative outcomes.…”
Section: Pl::dms Pathways Divergently Control Response Strategies To Positive and Negative Outcomessupporting
confidence: 58%
“…S7). To analyze effects on choice selection, we took advantage of the strong dependence on prior trial outcomes 27,28 , analyzing win-stay and lose-stay probabilities (see Methods). We found no evidence that optogenetic inhibition of PL::A-DMS throughout the choice period had any impact upon ongoing action selection (Fig.…”
Section: Pl::a-dms Pathways Mediate Future Choice Valuation But Not Current Choice Executionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this selective decrease in cortical-iSPN excitatory drive is expected to promote disinhibition of thalamic structures projecting back to the cortex. It is an interesting future question as to whether this thalamic disinhibition can explain both simple motor phenotypes (e.g., hyperactivity, aggression) ( Etherton et al, 2009 ; Grayton et al, 2013 ) and more complex reward-processing deficits observed in mice with Nrxn1α mutations ( Alabi et al, 2020 ). It is worth noting a recent study of the Tsc1 deletion ASD mouse model, which exhibited increased corticostriatal connectivity selectively onto dSPNs, with synaptic strength unperturbed at thalamostriatal synapses ( Benthall et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they show stereotypic and repetitive behaviors such as increased grooming, impaired nest-building, altered novelty responsiveness, and habituation [ 31 , 35 , 38 ]. In addition, several behaviors were reported that relate to ASD comorbidities including deficits in learning and cognition, locomotor activity, motor performance, award processing, and anxiety-like behaviors [ 31 , 35 , 36 , 38 , 46 , 47 , 48 , 49 ]. Although the social, stereotyped, and repetitive behaviors are commonly studied, sensory behaviors have received less attention in this model.…”
Section: From Human Asd Genetics To Translational Behavioral Phenotype In Mouse Modelsmentioning
confidence: 99%